Formation of creative thinking of a lawyer in modern conditions of development including the influence of COVID-19 pandemic - Alazzam, Farouq Ahmad Faleh; Alshunnaq, Mueen Fandi Nhar (Creativity Studies, 2023)
The main purpose of the study is to determine the principal ways of forming creative thinking among lawyers in their practice in modern conditions of development under the influence of COVID-19 pandemic. The importance of studying creative thinking and its formation is determined because the study of this problem creates the basis for the formation of a psychological attitude towards the creative development of a personality, which will be able to effectively solve non-standard problems of legal science and practice. The leading direction of training a future lawyer is the disclosure and activation of creative potential. In this process, focus on the attitudinal sphere of the personality is because it determines the activation of professional creativity and contributes to the disclosure of the creative potential of a specialist. As a result of the study and the application of the proposed methodology, the main stages were identified to promote the development of creative potential and thinking among lawyers in modern conditions of development, considering the impact of COVID-19 pandemic. The proposed research results may have a practical aspect of implementation in the activities of a modern lawyer.